Perencanaan Pompa untuk Mempercepat Waktu Pengisian Oli di PT KSB Indonesia - Fitrianti Sugiono, Friska; Abidin, Zaenal; Asmara, Dewa (Universitas Nusa Putra, 2024)
In this study, specifications & design of the pump to used will be analyzed, then performance the oil pump is known, and effect of the oil pump on the ISP 3600 Trailer pump assembly process is analyzed. This research method begins with problem identification, literature study, analysis & optimization, design planning, fabrication process, assembly process and testing, then analyzed to obtain results in accordance with the objectives. Results this testing use a gear pump with minimum power of 67.15 Watts, using electric motor that has a minimum torque of 1.081 N.m and minimum power of 0.2125 HP, and using minimum capacitor capacity of 24.31 µF. This test uses Fuchs Renolin B46 Plus oil. Results this testing obtain a discharge of 16.789 l/min and charging time of 12.21 minutes per 205 liters.